ANALISIS MOTIVASI DALAM MENINGKATKAN KINERJA PETUGAS KESEHATAN DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS TAMIANG LAYANG KAB. BARITO TIMUR - -, Novria Pangamiani (Jurnal Ilmiah Ekonomi Bisnis, 2023)
The purpose of this study was to find out the provision of motivation to improve the performance of UPTD health workers at the Tamiang Layang Health Center so far and what it should be. This study uses a qualitative method with a descriptive approach. This study used a population of 35 UPTD employees at the Tamiang Layang Health Center in 2023. The sample in this study used a saturated sample. This sampling technique is carried out when all members of the population are used as samples, consisting of 2 general practitioners, 1 dentist, 13 nurses, 3 dental nurses, 7 midwives, 2 sanitarians, 2 pharmacists, 2 analysts. health, 3 nutritionists. Data collection techniques using observation, questionnaires and interviews. The results of the study show that the motivations in the UPTD Tamiang Layang Health Center so far are absences, allowances or incentives, and services, while the motivation that should be is the implementation of financial motivation consisting of salary, bonuses, and social security. While non-financial motivation is the work environment, awards and praise.